SIFAT PAPAN PARTIKEL DARI LIMBAH EKSPLOITASI - Rozak Memed; I M Sulastiningsih (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
The result of a study on the properties of particle board made from logging waste is reported in this paper. The wood species used in the study as raw material for particle board are meranti (Shorea sp.), ramin (Gonystylus bancanus Kurz.) and combination  of the two species. The result shows that wood species and particle size has a significant effect on the water absorption and thickness